The making of a doctor: the matrix and self. (September 2019) - Gerada, Clare
Foulkes' concept of the matrix, the hypothetical web of communication, has long since left the consulting room and entered the wider sphere of communities, countries, and institutions. This article will discuss how the matrix encompasses a whole profession, that of medical doctors. Together with a deep-rooted sense of identity, which I refer to as the medical self, the medical matrix contributes to doctors' professional wellbeing but also begins to explain the enormous recent increase in mental illness in the medical profession seen across the world. The article focuses on doctors. However, the ideas are relevant to any group (for example, teachers, the clergy, psychotherapists) which has a strong personal and professional identity, with all its attendant privileges and problems.